Metode Latihan Small Sided Game dengan Rasio Interval 1:1 untuk Meningkatkan Kapasitas Aerobik Pemain Sepak Bola Manggalapati FC - Shandy, Dwi Kurnia (MAN Insan Cendekia Jambi, 2025)
The purpose of this study was to determine the effect of small-sided games training with a 1:1 ratio interval on aerobic capacity. This type of research is experimental, the research method uses true experimental with randomized control group pretest-posttest. Data analysis used is the mean, standard deviation, normality test, paired sample t-test. The results of this study are from the paired sample t-test The results showed that small-sided games training with a 1:1 ratio interval can provide a significant increase (p = 0.000 <0.05) with an average increase of 9.37. It can be concluded that there is an effect of aerobic capacity with the small-sided games training method with a 1:1 interval ratio on Manggalapati FC soccer players.